A case report of incidental finding of concrescence teeth on a panoramic radiograph as a complication of impacted maxillary third molar - Agustin, Sylvia; Epsilawati, Lusi; Sitam, Suhardjo; Rante Marampa, Wilman (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: Concrescence is a rare dental developmental anomaly where two fully formed teeth are fused by cementum. It often occurs in the maxillary posterior region and may lead to tooth impaction. This case report presents an incidental radiographic finding of a concrescence related to maxillary third molar (M3) impaction. Case Report: A 72-year-old woman presented with a panoramic radiograph referral for mandibular denture placement with a clinical diagnosis of missing teeth in the right and left mandibular regions. On the panoramic radiograph, the impacted root of tooth 28 was seen, fused with the root of tooth 27. Conclusion: Concrescence is a rare case of anomaly and can occur in an impacted M3 tooth, and Concrescence is suspected as the main cause of the tooth not being erupted/impacted. Keywords: Concrescence, maxillary molar tooth impaction, panoramic radiography